2021
DOI: 10.1111/acel.13468
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the cGAS‐STING pathway ameliorates the premature senescence hallmarks of Ataxia‐Telangiectasia brain organoids

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 43 publications
3
40
0
Order By: Relevance
“…In the disease context of AT syndrome, which presents striking phenotypic similarities to FA, cGAS is engaged during the senescence of AT patients olfactory neurosphere-derived cells and brain organoids, which display micronuclei. Importantly, cGAS and STING inhibition in this model prevents astrocyte senescence and protects brain organoids from neurodegeneration (Aguado et al, 2021). Given that FA syndrome was recently described as a 'senescence syndrome' (Helbling-Leclerc et al, 2021), the premature ageing observed in FA might also be an important source of IFN-I production.…”
Section: Accumulation Of Cytosolic Dna During Senescence Drives Ifn-i...mentioning
confidence: 90%
See 1 more Smart Citation
“…In the disease context of AT syndrome, which presents striking phenotypic similarities to FA, cGAS is engaged during the senescence of AT patients olfactory neurosphere-derived cells and brain organoids, which display micronuclei. Importantly, cGAS and STING inhibition in this model prevents astrocyte senescence and protects brain organoids from neurodegeneration (Aguado et al, 2021). Given that FA syndrome was recently described as a 'senescence syndrome' (Helbling-Leclerc et al, 2021), the premature ageing observed in FA might also be an important source of IFN-I production.…”
Section: Accumulation Of Cytosolic Dna During Senescence Drives Ifn-i...mentioning
confidence: 90%
“…Notably, genetic depletion of cgas (Gray et al, 2015), sting (Gall et al, 2012), irf3 or ifnar (Stetson et al, 2008) inhibits the IFN-I response and relieves autoinflammatory symptoms, confirming the important contribution of IFN-I to AGS pathology. AT syndrome is, on the other hand, more closely related to FA pathophysiology and also relies on chronic STING activation (Hartlova et al, 2015;Aguado et al, 2021). AT is caused by mutations in the Ataxia-Telangiectasia-Mutated kinase (ATM), a master regulator of DNA repair.…”
Section: Constitutive Activation Of Ifn-i In Dna Repair and Dna Metab...mentioning
confidence: 99%
“…The expression of ATM (ataxia telangiectasia mutated), a DDR gene and a key initiator of DNA repair, is decreased in old mouse fibroblasts and brain tissues [ 32 , 33 ]. In mice with ataxia telangiectasia, the ATM mutation results in DNA repair deficiency and an accumulation of DNA fragments; this activates the cyclic GMP–AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling, a DNA fragment sensor system, and triggers chronic inflammation as well as premature senescence in the central nervous system (CNS) [ 34 ]. Telomere repeat binding factor 2 (TRF2), which is essential for maintaining the structure and function of telomeres, is down-modulated and impaired during aging.…”
Section: The Signaling Pathways Associated With Neuronal Senescence and Brain Agingmentioning
confidence: 99%
“…Ataxia-Telangiectasia (A-T), a genome instability disorder caused by biallelic mutations in the ataxiatelangiectasia mutated (ATM) gene, is a premature aging Editorial syndrome that in many aspects recapitulates human brain aging [7]. In a recent paper we established a model of human accelerated brain aging using BOs generated from induced pluripotent stem cells derived from Ataxia-Telangiectasia (A-T) patient cells [8]. As compared to healthy wild type counterparts, A-T BOs display multiple hallmarks of aging, including SASP activation, lamin B1 downregulation, micronuclei accumulation, and increased senescence-associated βgalactosidase (SA-β-gal) activity; phenotypes that appeared enriched in astrocyte populations [8).…”
mentioning
confidence: 99%
“…In a recent paper we established a model of human accelerated brain aging using BOs generated from induced pluripotent stem cells derived from Ataxia-Telangiectasia (A-T) patient cells [8]. As compared to healthy wild type counterparts, A-T BOs display multiple hallmarks of aging, including SASP activation, lamin B1 downregulation, micronuclei accumulation, and increased senescence-associated βgalactosidase (SA-β-gal) activity; phenotypes that appeared enriched in astrocyte populations [8). This observed premature aging phenotype was shown to be dependent on the cGAS-STING signalling axis, as inhibition of either cGAS or STING was sufficient to not only significantly reduce the SASP, but to also reduce the number of senescent cells as measured by CDKN1A and SA-β-gal positive cells [8].…”
mentioning
confidence: 99%